Chinese Cultural Acculturation and Religious Inculturation at Santa Maria de Fatima Catholic Church and Dharma Toasebio Temple - Angela Fransisca Sabrina Panggabean; Yang Nadia Miranti (Lembaga Riset Ilmiah, 2026)
This study investigates the acculturation of Chinese culture within the architectural visual identity and religious inculturation at Santa Maria de Fatima Catholic Church and Dharma Toasebio Temple in Jakarta. It compares how both institutions sustain their ethnic identity and spiritual functions within a pluralistic urban society. The originality of this work stems from its comparative framework, contrasting internal acculturation with contextual inculturation. It specifically highlights how architectural elements act as social instruments to negotiate identity within a multicultural environment. A descriptive comparative qualitative method was employed, utilizing literature reviews, digital site observations of the two primary buildings (n=2), and visual semiotic analysis. Results indicate that Dharma Toasebio Temple reflects internal acculturation through its Tri Dharma architecture, which is characterized by red and gold color schemes and swallowtail roofs. Conversely, Santa Maria de Fatima Church appropriates the design of a Chinese aristocratic residence to contextualize the Catholic faith. These distinctions demonstrate that such visual components extend beyond mere decoration; they serve as a community strategy to maintain social cohesion and spirituality in dynamic public spaces. Consequently, the findings expand the current understanding of cultural integration within urban religious architecture. Ultimately, both sites achieve a harmonious synthesis of religious conviction and ethnic identity through Chinese cultural symbols. This integration theoretically advances visual semiotics while practically reinforcing social cohesion and interfaith tolerance in an urban setting.